ANALISIS SEBARAN TAPIR TENUK DI INTENSIVE PROTECTION ZONE TAMAN NASIONAL BUKIT BARISAN SELATAN - Purwati, Indah; Ahyuni, Ahyuni (JURNAL BUANA, 2026)
The existence of forest fragmentation with the construction of five major roads in Bukit Barisan Selatan National Park will affect the quality and quantity of animal habitats. Fragmentation will reduce connectivity and dispersal of animals, becoming a barrier to movement in search of food and mates. In conservation planning, information on the distribution of animals is useful to determine the presence of animals and is used to determine the appropriate habitat for these animals. The purpose of the study was to determine the distribution of tapir tenuks in the IPZ of Bukit Barisan Selatan National Park by using the Kernel Density method, which is a type of density that uses a non-parametric statistical formula to estimate density using data on the presence of tapir tenuks based on patrols and camera traps. From the results of the research, based on camera trap data, tapir tenuk is highly distributed at the Sukaraja Atas resort, based on patrol data, which is highly distributed in Balik Bukit, Biha, and Suoh, and when combined tapir tenuk is found in all resorts except Balai Kencana which has the lowest distribution.